SEROPREVALENCE AND RISK FACTORS ASSOCIATED WITH HPV INFECTIONS AMONG PATIENTS IN KOGI EAST SENATORIAL ZONE - AWULU, OLOBO F.; Aminu, Maryam; SULEIMAN, A. B.; MAKOLO, DANIEL (FUDMA JOURNAL OF SCIENCES, 2020)
Analysis of prevalence and risk factors for Human Papilloma Virus (HPV) is the basis for prophylactic strategies against HPV infections. This study was to determine the seroprevalence of human papillomavirus, sociodemographic and risk factors associated with acquiring the virus among the study population. A total of 195 samples were collected by simple random sampling technique from three major hospitals in the zone. Serum from blood samples was used for ELISA and analyzed for IgM. Overall prevalence of 3.08% (6/195) was established for HPV infection. Patients with early sexual activity and those with multiple sexual partners were likely to be infected than their counterparts with 15.8%: 3/19 (Ï‡ 2 =16.4, df=3, p=0.001) and 50%: 2/4 (Ï‡ 2 =30.2, df=1, p=0.005) respectively. The infection was more among those who got married at age range of 26-30 years with prevalence of 5.4%: 2/37 (Ï‡ 2 =1.30, df = 5, p=0.82). On the basis of sex, female were found to have higher prevalence of 3.6%: 6/167(Ï‡ 2 =1.04, df = 1, p=0.6). Subjects with sexually transmitted disease (STD) had a higher prevalence of 8%: 2/25(Ï‡ 2 =2.45, df=2, p=0.32). The study shows that infection with HPV was strongly associated with age of sexual debut and number of sexual partners. It also reveals the occurrence of HPV infection in Kogi East, Nigeria. Hence, there is need for routine screening, public education and vaccination to prevent the spread of the virus which is a threat to public health.